2021
DOI: 10.4254/wjh.v13.i11.1653
|View full text |Cite
|
Sign up to set email alerts
|

Fungal infections following liver transplantation

Abstract: With increasing morbidity and mortality from chronic liver disease and acute liver failure, the need for liver transplantation is on the rise. Most of these patients are extremely vulnerable to infections as they are immune-compromised and have other chronic co-morbid conditions. Despite the recent advances in practice and improvement in diagnostic surveillance and treatment modalities, a major portion of these patients continue to be affected by post-transplant infections. Of these, fungal infections are part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
0
8
0
3
Order By: Relevance
“…Thus, fluconazole is still the most viable option in the public system. [46][47][48][49]55 In LgT, recent and past studies suggest using azoles as the prophylactic agents. Similarly, a recent study places azoles as first-line antifungal agents in 80% of cases, echinocandins in approximately 18.3%, and amphotericin B in only 1.5%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, fluconazole is still the most viable option in the public system. [46][47][48][49]55 In LgT, recent and past studies suggest using azoles as the prophylactic agents. Similarly, a recent study places azoles as first-line antifungal agents in 80% of cases, echinocandins in approximately 18.3%, and amphotericin B in only 1.5%.…”
Section: Discussionmentioning
confidence: 99%
“…As for liposomal amphotericin, although this drug does not alter the cytochrome P450 system, its nephrotoxicity has been and continues to be a major concern. [46][47][48][49][50]52 It is also important to note that there is still no consensus on the need for antifungal prophylaxis in all transplant patients. Several programs do not routinely use antifungals perioperatively in these patients, and one study showed a similar incidence of IFI in the absence of prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Ademais, um trabalho mais recente de revisĂŁo gerido por Khalid et al sugeriu que a eficĂĄcia do fluconazol era semelhante Ă  da anfotericina lipossomal, porĂ©m que o fluconazol seria preferencial devido ao seu custo-benefĂ­cio e perfil de segurança. 48 Ainda sobre o TF, uma pesquisa de Kang et al mostrou que a micafungina poderia ser usada como alternativa ao fluconazol, nĂŁo havendo diferença entre ambos em termos de presença de IFI, tempo para desenvolvimento de IFI, sobrevida livre de fungos e reaçÔes adversas. A pesquisa ainda verificou semelhantes taxas de sucesso clĂ­nico de 95,65% e 96,10%, nos grupos de micafungina e fluconazol, respectivamente.…”
Section: Profilaxia De Ifi Em Tosunclassified
“…Assim, o fluconazol ainda parece ser a opção mais viĂĄvel no sistema pĂșblico. [46][47][48][49]55 No TP, tanto estudos recentes como estudos passados sugerem o uso de azĂłis como os agentes profilĂĄticos. Da mesma forma, um estudo recente coloca os azĂłis como agentes antifĂșngicos de primeira linha em 80% dos casos, jĂĄ as equinocandinas em aproximadamente 18,3% e a anfotericina B somente em 1,5%.…”
Section: DiscussĂŁo E ConclusĂŁounclassified